ASPECTS OF PRODUCTION AND MARKETING BUSINESS FEASIBILITY TOFU AND TEMPEH MSMES - Rahman, Fadali; Lestari, Dian; Nurfaizah, Arini; Fikni, Nurinda Aulia; Naila, Alfin (Multifinance, 2025)
This study aims to analyze the production and marketing aspects as key indicators of business feasibility for tofu and tempeh MSMEs (Micro, Small, and Medium Enterprises) in Teja Village, Pamekasan Regency, Indonesia. The business involves traditional soybean processing into high-value food products while maintaining a strong market orientation. Based on field observation and interviews, the enterprise operates four times a week, producing approximately 30 kg of tofu and 30 kg of tempeh per day. With an initial capital of less than IDR 50 million, it qualifies as a micro-enterprise. This study employs a qualitative descriptive approach, utilizing SWOT analysis and a basic feasibility analysis based on production efficiency, market potential, and direct marketing strategies. The findings reveal that the business is feasible and promising for further development, especially due to stable local demand and low per-unit production costs. These insights offer valuable contributions to MSME development strategies that leverage local potential and operational efficiency. The study recommends adopting digital marketing innovations and modernizing equipment to enhance competitiveness and expand market reach.